Co-Sintering Study of Na0.67[Ni0.1Fe0.1Mn0.8]O2 and NaSICON Electrolyte–Paving the way to High Energy Density All-Solid-State Batteries - Dück, Gerald; Naqash, Sahir; Finsterbusch, Martin; Breuer, Uwe; Guillon, Olivier; Fattakhova-Rohlfing, Dina (Frontiers in Energy Research, 2021)
Sodium is a promising candidate for stationary storage applications, especially when the demand for lithium-ion batteries increases due to electromobility applications. Even though its energy density is lower, Na-ion technology is estimated to lead to a cost reduction of 30 % compared to Li-ion technology. To improve safety as well as energy density, Na-based all-solid-state-batteries featuring solid electrolytes such as beta-alumina and sodium superionic conductors and cathode materials such as Na3V2(PO4)3 and NaxCoO2 have been developed over the past years. However, the biggest challenge are mixed cathodes with highly conductive interfaces, especially when co-sintering the materials. For example, a promising sodium superionic conductor type Na3Zr2Si2PO12 electrolyte sinters at 1250 °C, whereas the corresponding Na3V2PO12 cathode decomposes at temperatures higher than 900 °C, posing a bottleneck. Thus in this paper, we synthesized Na0.62[Ni0.10Fe0.10Mn0.80]O2 as cathode material for all-solid-state sodium-ion batteries via a relatively cheap and easy solution-assisted solid state reaction processing route. The thermal investigations of the pure cathode material found no degradation up to 1260 °C, making it a perfect match for Na3.4Zr2Si2.4P0.6O12 electrolyte. In our aim to produce a co-sintered mixed cathode, electron microscopy investigation showed a highly dense microstructure and the elemental mapping performed via energy dispersive X-ray spectroscopy and secondary ion mass spectrometry confirm that Na3.4Zr2Si2.4P0.6O12 and Na0.62[Ni0.10Fe0.10Mn0.80]O2 do not react during sintering. However, the active cathode material forms a sodium rich and a sodium deficient phase which needs further investigation to understand the origin and its impact on the electrochemical performance.